Performance Evaluation of Backend Frameworks for REST API: A Comparative Study of Spring Boot, Flask, Express.js, Laravel FrankenPHP, and Gin - Azzahidi, Aufa Syaihan; Wijayanto, Bangun; Darmawan, Agus (Informatika, Universitas Jenderal Soedirman, 2025)
One major impact of this development is the shift in application development, particularly in data integration across different platforms. Web services have emerged as a solution for system integration and multi-platform application development. One implementation of Web services is Representational State Transfer. The choice of programming language and framework is also crucial in web application development, directly affecting performance and efficiency. Research on framework performance is necessary to support the development of an Academic Information System. This study will use parameters such as response time, throughput, and resource usage, employing a performance testing method modified by the author. The method includes problem identification, data collection, backend development, performance testing, and conclusion. The test results show that Spring Boot outperforms others in all parameters with stable and efficient performance. Gin is suitable for medium-scale data, Flask excels in scalability but lacks stability, Express.js is efficient CPU usage, and Laravel with FrankenPHP is Memory-efficient. These results serve as a reference for selecting frameworks according to REST API development needs. This research supports developers in selecting appropriate backend frameworks for high-performance REST API systems.